Develop an indirect ELISA utilizing gD protein to detect antibodies against bovine herpesvirus type 1 - Liu, Qiang; Liang, Ruijin; Niu, Xiaoxia; Jiang, Lingling; Zhang, Gang; Wang, Pu; Zhang, Sinong; Gao, Weifeng; Wang, Yujiong; Guo, Huichen; Li, Yong (Frontiers in Cellular and Infection Microbiology, 2025)
Bovine herpesvirus type 1 (BHV-1) is a highly contagious DNA virus that causes a variety of diseases affecting the reproductive and respiratory tracts. These diseases can reduce the health and production performance of cattle, causing significant economic losses in the cattle industry. The current ELISA kits used to detect BHV-1 have long lead times and are expensive, and are not suitable for bulk testing on large farms. therefore, there is an urgent need to develop a rapid and cost-effective alternative to the BHV-1 test. In this study, recombinant gD protein was expressed by prokaryotic system, and then used as antigen to immunize New Zealand white rabbits to obtain polyclonal antibodies (pAb). An indirect enzyme-linked immunosorbent assay (iELISA) based on gD protein was established for the detection of BHV-1 antibodies in clinical samples. The optimal cutoff value was determined to be 0.6185 using 60 clinical serum samples. This method had no cross-reaction with other common bovine viruses. The developed iELISA method and commercially available kits were used to detect 60 bovine serum samples, with a concordance rate of 93.3%. In summary, we established a rapid and reliable iELISA method based on gD protein, which is suitable for epidemio-logical monitoring of BHV-1.